Especies forestales amenazadas y en peligro de extinción de la guardiana Lumber del parque nacional Cotacachi cayapas, provincia de Esmeraldas. Año 2019 - Corozo Nazareno, Alcívar Manuel (2020)
The main threat faced by forest species in Ecuador is habitat loss, caused by human activities. The greatest impact comes from small or large-scale deforestation, either for timber or firewood extraction, or for the change of land use for agriculture, livestock, urbanization or mining, which has caused some species to be in danger to disappear. Due to this, an investigation was carried out in the Lumber Guardian of the Cotocachi-Cayapas National Park in the province of Esmeraldas, where the objectives were to evaluate the structure and composition of the forest, what is the phenology of threatened forest species. What is the natural regeneration potential of the species and develop a forest recovery plan as a strategy for the conservation of threatened forest species, the sampling design was established completely at random, the evaluation of the horizontal and vertical structure was considered, it was carried out a survey of the inhabitants to know the species of the forest and guarantee a regeneration of the species, finally a proposal was made for training the inhabitants. A total of 17 families were identified where the most representative was Fabaceae with 44 individuals, in the sampling units 233 individuals belonging to 47 species were registered, in the absolute and relative abundance of species it was found that, the most common species among the units samples were Anacardium excelsum, Inga sp., Hevea brasiliensis and Virola dixonii, Anacardium excelsum species with 17 and 12.69%, Hevea brasiliensis with 10 and 7.46%, Inga sp. with 10 and 7.46% and Schizolobium parahybum with 10 and 7.46%, obtained a remarkable absolute and relative frequency. The importance value index of the sampling units in general indicated Schizolobium parahybum, Anacardium excelsum and Carapa guianensis as the most representative species. In the vertical structure, the upper stratum was where the largest number of individuals were reported. The Simpson diversity index expressed the highest values of 0.895 and 0.861 with a Jaccard similiride index of 0.615. The species that were reported in danger were: chanul Humiriastrum procerum; cedar Cedrela odorata L; guayacán pechiche Minquartia guianensis; guangare Otoba gracilipes; tangare Carapa megistocarpa; chalviande Virola dixonii; guadaripo Nectandra guadaripo; Parinari romeroi toad leather.